Translation of Cellular Senescence to Novel Therapeutics: Insights From Alternative Tools and Models - Inci, Nurcan; Kamali, Dilanur; Akyildiz, Erdogan Oguzhan; Tahir Turanli, Eda; Bozaykut, Perinur (Frontiers in Aging, 2022)
Increasing chronological age is the greatest risk factor for human diseases. Cellular senescence (CS), which is characterized by permanent cell-cycle arrest, has recently emerged as a fundamental mechanism in developing aging-related pathologies. During the aging process, senescent cell accumulation results in senescence-associated secretory phenotype (SASP) which plays an essential role in tissue dysfunction. Although discovered very recently, senotherapeutic drugs have been already involved in clinical studies. This review gives a summary of the molecular mechanisms of CS and its role particularly in the development of cardiovascular diseases (CVD) as the leading cause of death. In addition, it addresses alternative research tools including the nonhuman and human models as well as computational techniques for the discovery of novel therapies. Finally, senotherapeutic approaches that are mainly classified as senolytics and senomorphics are discussed.